Incidence and features of preoperative anxiety in patients undergoing elective non-cardiac surgery - Kuzminskaitė, Vilma; Kaklauskaitė, Justina; Petkevičiūtė, Justė (Acta medica Lituanica, 2019)
The study was conducted at the Centre of Anaesthesiology, Intensive Care and Pain Management of Vilnius University Hospital Santaros Klinikos. Background. Due to its implications on postoperative outcomes and patient satisfaction, anxiety evaluation should be incorporated in the preoperative assessment of the patients. Materials and methods. A series of consecutive patients undergoing elective surgery were included in the study. Preoperative anxiety was evaluated using the Hospital Anxiety and Depression Scale (HADS), the Amsterdam Preoperative Anxiety and Information Scale (APAIS), and the Visual Analogue (Face) Scale (VAFS). Qualitative and quantitative analyses were used to describe features of anxiety. Results. 149 patients were included in the study, of whom 40.9% were scheduled for low, 47.7% for intermediate, and 11.4% for highrisk procedures. Based on HADS, 19 patients (12.6%) were positive for anxiety. VAFS revealed that 10.3% of patients experience medium/high intensity of anxiety. Patients were mostly concerned about the success (29.3%) and complications (11.4%) of the surgery APAIS score analysis revealed significantly higher anxiety (p < 0.01) and a need of information (p < 0.01) about surgery compared to anaesthesia. In contrast to age, education, or previous surgery, anxiety was associated with female sex (p < 0.01), surgical risk (p = 0.02), and subjective health evaluation (p < 0.01). Patients tended to choose a conversation with the doctor (45.6%) or a relative (44.8%) as a measure to relieve anxiety, and 18.4% would choose medication. Praying, music therapy, massage, or even sexual intercourse were among the measures suggested by patients. Conclusions. A significant part of patients experience anxiety before surgery, predominantly about the success of the surgery. According to the patients, conversation is the best option to reduce anxiety.